Prevalência de doença falciforme no estado de Mato Grosso a partir de dados de triagem neonatal - Castro, Gabrielle Pinheiro de (2018)
Sickle cell disease (SCD) is a generic term that includes a group of hereditary hemolytic anemias characterized by hemoglobin S. Its origin is through a point mutation that causes alteration in the amino acid sequence of the hemoglobin β chains, causing the production of hemoglobin variant (HbS). Epidemiological data regarding the pathology, its clinical manifestations, the need for diagnosis and its relationship with ethnicity and miscegenation, make SCD an important public health problem. Despite the existing studies about the disease in the Brazilian population, the issue remains scarce when it comes to updated regional prevalence data in the State of Mato Grosso (MT). The objective of the present study was to identify the prevalence of DF in the state of Mato Grosso through the Neonatal Screening Reference Service of the University Hospital Júlio Müller (SRTN-HUJM) according to data collected in the period from 2010 to 2016. The increasing records of the number of cases of sickle cell trait in the state and among the regional health offices in relation to cases of sickle cell anemia and other hemoglobinopathies were one of the main aspects identified in the study. The age at which the evaluated children received the test result was also checked. It was observed that children diagnosed with sickle-cell anemia took longer to receive the result than children with other hemoglobinopathies with less severe symptomatology. In relation to the neonatal screening tests among live births, the average coverage of 73.3% in the State was observed. Regarding the age group that the children undergo the neonatal screening, a larger number of children were examined after seven days of birth, and the National Neonatal Screening Program (PNTN) recommended that this occur between the third to fifth day. The average time from the test to the release of the result is another fact that calls attention. The results show that the number of cases of sickle cell traits was high and in significant growth, demonstrating that both in the country and in the MT state, miscegenation is the factor responsible for the transmission and perpetuation of HbS. The studies also showed that the cases of SCA were the third most frequent hemoglobinopathy in the state, with a percentage of 0.82%, setting a future concern regarding the increase in the number of cases and morbidity and mortality due to SCA.